Implementing the Love Method in Moral Education to Foster Students’ Positive Character - Supriyanto; Sumaryati; Zuhri; Kasor, Ahamakosee (Universitas Islam Negeri Raden Intan Lampung, 2026)
Moral education in Islamic Religious Education at the secondary school level still tends to emphasize memorization and content mastery, causing students to understand values cognitively without consistently demonstrating them in daily behavior. This study examines the implementation of the Love Method in line with the Love-Based Curriculum, an educational approach that places compassion, respect for students’ dignity, psychological safety, and positive discipline at the center of learning, and its contribution to fostering students’ positive character at Public senior high school (SMAN) 5 Tanjungpinang. A qualitative approach with a case study design was employed to gain an in-depth understanding of classroom practices in the school’s natural setting. The participants consisted of two Islamic Religious Education teachers, two homeroom teachers, one vice principal for student affairs, and fifteen students. Data were collected through observation, in-depth interviews, narrative questionnaires, and document analysis, then analyzed thematically using source and technique triangulation. The findings show that the Love Method was implemented through empathy, courteous communication, positive reinforcement, role modeling, and relational restoration, which encouraged students to become more polite, disciplined, honest, responsible, and sensitive to their peers. These outcomes were supported by teacher collaboration, school support, and parental involvement, although limited time, old teaching habits, and inconsistent implementation remained key challenges.